Cognitive fatigue in older adult university educators during psychoadaptation to digital environments - Carlos Armando Huamán Carreón; Ramiro Amílcar Bolaños Calderón; George Argota Pérez; Juan Benites Noriega; Richard Condori Cruz; Jesus Esteban Castillo Machaca; Milthon Quispe Huanca; Ramiro Madonio Yallico Calmett (Universidad de Ciencias Médicas de La Habana, 2024)
Introduction: Mental fatigue leads to a decline in teaching performance in response to the demands of online education. Objective: To assess cognitive fatigue in elderly university educators during psychoadaptation to digital environments. Material and Methods: A total of 27 elderly university educators were surveyed online from January to June 2023. A Likert scale was utilized, and reliability was validated using Cronbach's alpha coefficient. The Spearman correlation between cognitive fatigue and psychoadaptation to digital environments was analyzed using SPSS v25. The results were considered significant when p≤0.05. Results: Elderly university educators face difficulties with digital technology: concentration problems (88.9%), mental exhaustion (77.8 %), resistance to digitized tasks (70.4 %), lack of tool security (66.7 %), and work overload (81.5 %). Cognitive fatigue and deficient adaptation (score of 3.25) highlight the need for specific support. Data reliability (α = 0.73) supports cognitive fatigue measurement. The correlation between cognitive fatigue and digital adaptation is weak and nonsignificant (ρ = 0.2563, p = 0.2768), suggesting a complex relationship. Conclusions: There are significant challenges to the adaptation of elderly university educators to digital technology, emphasizing the need for specific support and appropriate strategies.